Combination of a high-carbohydrate diet and streptozotoc in for modeling type 2 diabetes in Wistar rats - S. V. Ivanov; R. U. Ostrovskaya (Фармакокинетика и Фармакодинамика)
Relevance. To conduct a preclinical evaluation of the effectiveness of antidiabetic drugs, models simulating the pathogenesis and main manifestations of diabetes mellitus (DM) in humans are needed. The streptozotocin (STZ) model, which has received the most widespread use in the experiment, does not allow reproducing the stepwise multifactorial development of type 2 diabetes. Goal. To develop a model of type 2 diabetes using a high-carbohydrate diet in combination with a subthreshold dose of STZ in Wistar rats, characterized by hyperglycemia and insulin resistance. Methods. The animals of the control group (n = 20) received water as a drink, and the experimental group (n = 20) received a 10 % solution of fructose. After 14 days, 10 animals from each group were injected with STZ at a dose of 35 mg/kg. The blood glucose level was determined weekly. To assess insulin resistance, a oral glucose tolerance test was performed before and after the administration of STZ. Results. It was found that keeping rats on a high-carbohydrate diet for two weeks leads to a violation of glucose tolerance, which indicates insulin resistance. The introduction of STZ at a subthreshold dose of 35 mg/kg to animals on a standard diet causes an increase in the glycemic drop to 13.2 mmol/l, while the same dose of STZ against the background of a high-carbohydrate diet causes an increase in the level of hyperglycemia to 22.9 mmol/l and increases insulin resistance. Conclusion. The synergism of a high-carbohydrate diet and low doses of STZ makes it possible to obtain a model of type 2 diabetes mellitus that reproduces not only basal hyperglycemia, but also impaired glucose tolerance, which more fully corresponds to the process of developing type 2 diabetes in humans.